Bahasa Inggris untuk Broadcasting : Materi Pengajaran Need Analisis - Masitoh; Oktavia, Diana; Trisnawati, Winda (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
English plays a significant role in the broadcasting industry, particularly in mastering software, technical terminology, and professional communication skills. However, at SMKS Islam Andalusia, the English teaching materials currently used remain general and are not fully aligned with the specific needs of the Broadcasting concentration. This study aims to analyze the English teaching material needs that match broadcasting competencies in order to support the learning process while also preparing students for the workplace. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews with the English teacher, broadcasting teachers, and the school principal. Thematic analysis was applied to identify themes emerging from the data. The findings indicate that English materials should emphasize technical vocabulary related to broadcasting equipment and software, as well as skills in scriptwriting and news reporting, accompanied by speaking practice in professional contexts. In conclusion, the existing materials are still too general and do not adequately meet students’ specific needs. Therefore, the development of teaching materials based on English for Specific Purposes (ESP) is essential to ensure learning becomes more contextual, vocationally oriented, and supportive of students’ readiness to face the challenges of the broadcasting industry.